THE EFFECT OF PESTICIDES ON THE DIGESTIVE ORGANS OF YOUNG CHILDREN IN KARAKALPAKSTAN (Konferensiyalar | Conferences, 2024)
This article aims to delve into the intricate relationship between pesticide use and the health of young children in Karakalpakstan, specifically focusing on the effects of pesticides on their digestive organs. By exploring existing research, highlighting health concerns, and proposing actionable recommendations, this article seeks to raise awareness about the importance of safeguarding children's digestive health in the face of pesticide exposure in Karakalpakstan.